Efektivitas Implementasi Kebijakan Percepatan Penurunan Stunting di Kampung Keluarga Berkualitas Desa Mongpok Kabupaten Serang - Sururi, Ahmad; Malik, Abdul; Zainuri, Ahmad; Mulyasih, Rahmi; Berthanilla, Rethorika (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Accelerating the reduction of stunting requires synergistic implementation between various sectors, both at the central government level and regional and village governments. The purpose of this study was to find out the effectiveness of the Quality Family Village Program in Mongpok Village, Cikeusal District, Serang Regency in the Landscape of accelerated reduction of stunting. The research method uses a case study approach. Data collection techniques were carried out through interviews in Focus Group Discussion (FGD) activities which were carried out semi-structured with open questions. Data analysis uses systematic qualitative data analysis through the process of data classification (data coding), labeling, and category preparation. The results showed that the implementation of the accelerated stunting reduction policy in the Quality Family Village (KB) of Mongpok Village was based on an approach to changing the behavior of the target group, innovation in the implementation of the Family Planning Village, the effectiveness of government support and the impact of program implementation had been quite effective. Factors that support the success of reducing accelerated stunting in KB Village, Mongpok Village, Cikeusal District, as well as research findings, namely responsive leadership, stakeholder commitment, collaboration, awareness, and community compliance which have an impact on increasing public health status.Keywords: Effectiveness, Policy Implementation, Stunting, Family Planning Village, Mongpok Village